MANAJEMEN BISNIS : TINJAUAN ATAS PERLAKUAN AKUNTANSI ASET BIOLOGIS BERDASARKAN PSAK NO.69 - Nur’i Hidayatus Shalichah (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2022)
The accounting treatment of agricultural businesses should be in accordance with the reference to PSAK No. 69 on accounting for biological assets in agriculture. This paper aims to analyze comparatively PSAK No. 69 on UD. Barokah and UD. Makmur regarding the accounting treatment of biological assets using a qualitative approach and the type of case study. The results of the study are 1. The similarities between the two research objects are a) Standard financial reports for broilers by recording financial reports periodically every harvest (35 days). Biological assets come from outsiders by buying biological assets for maintenance and then selling them. Biological assets are measured by how much DOC yields and minus maintenance costs. The financial statements disclose the gains and losses for the current period. b). Broiler financial report standard UD. Barokah and UD. prosperous in accordance with PSAK 69, namely the statement of fixed assets is always recorded in each accounting period. Biological assets come from breeds not purchases. Agricultural assets are recognized by purchase or from crossbreeds from past events. Biological assets are measured at initial recognition and at the end of each reporting period at fair value less costs to sell. The presentation of biological assets in the financial statements is grouped under non-current assets. 2. Analysis of differences in recording biological assets of broiler chicken farms UD. Barokah and UD. Prosperity lies in the placement of the account. Financial reporting standards used by UD. Barokah is still simple and there are financial reports that have not applied applicable accounting standards. UD. Barokah does not record biological assets that have been classified in PSAK No. 69 (paragraph 43). The implication of this research is that the skill of recording financial statements is improved, in accordance with PSAK No. 69).